Lemna minor plants chronically exposed to ionising radiation: RNA-seq analysis indicates a dose rate dependent shift from acclimation to survival strategies. (April 2017) - Van Hoeck, Arne; Horemans, Nele; Nauts, Robin; Van Hees, May; Vandenhove, Hildegarde; Blust, Ronny
Graphical abstract: Highlights: RNA-seq analysis reveals dose rate dependent gene expression responses. The photosynthetic process is not affected under the tested exposure conditions. Low dose rates trigger the expression of flavonoid biosynthesis genes. High dose rates trigger responses frequently observed in acute radiation exposures. Results indicate a shift from acclimation response to survival response. Abstract: Ecotoxicological research provides knowledge on ionising radiation-induced responses in different plant species. However, the sparse data currently available are mainly extracted from acute exposure treatments. To provide a better understanding of environmental exposure scenarios, the response to stress in plants must be followed in more natural relevant chronic conditions. We previously showed morphological and biochemical responses in Lemna minor plants continuously exposed for 7 days in a dose-rate dependent manner. In this study responses on molecular (gene expression) and physiological (photosynthetic) level are evaluated in L. minor plants exposed to ionising radiation. To enable this, we examined the gene expression profiles of irradiated L. minor plants by using an RNA-seq approach. The gene expression data reveal indications that L. minor plants exposed at lower dose rates, can tolerate the exposure by triggering acclimation responses. In contrast, at the highest dose rate tested, a high number of genes related to antioxidative defense systems, DNA repair and cell cycle were differentially expressed suggesting that only high dose rates of ionising radiation drive L. minor plants into survival strategies. Notably, the photosynthetic process seems to be unaffected in L. minor plants among the tested dose rates. This study, supported by our earlier work, clearly indicates that plants shift from acclimation responses towards survival responses at increasing dose rates of ionising radiation.